Runnin' down a dream : how to thrive in a career you actually love - Gurley, Bill, 1966-; Mooney, Michael J. (Crown Currency, 2026)
"An unconventional, no-bullshit guide to forging a rewarding career that actually maps onto the things you care about in the world-a dream job where "the hustle doesn't feel like hustle"-from a leading venture capitalist, based on his viral college talk"-- Provided by publisher.